Empathy-Based Moral Education: A Comparative Study of Al-Attas’s Concept of Taʼdib and Hasan Al-Banna’s Concept of Tarbiyah from a Literature Review Perspective - Yulis Sutiani Sutiani; Mastora; Chusnul Khotimah Chotimah; Benny Prasetya (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2026)
Moral education in Islamic schools faces complex challenges amid globalisation, digital culture, value pluralism, and the weakening of students’ social-emotional awareness. This article presents a systematic conceptual literature review comparing Syed Muhammad Naquib Al-Attas’s concept of taʼdib and Hasan Al-Banna’s concept of tarbiyah as theoretical foundations for empathy-based moral education. Using an adapted systematic review protocol, relevant primary and secondary sources were identified, screened, and analysed thematically to examine the conceptual foundations, pedagogical implications, and points of convergence and divergence between the two thinkers. The findings show that taʼdib provides a strong epistemological and spiritual foundation for the formation of adab, moral consciousness, and proper recognition of human dignity, whereas tarbiyah offers a more operational communal framework through ukhuwwah, habituation, halaqah, and social responsibility. The main contribution of this article is an integrative model of Islamic empathic moral education that connects worldview formation, the internalisation of adab, relational practice, social-emotional learning, and reflective social action. This model strengthens Islamic moral education by combining philosophical depth with pedagogical strategies that can be implemented in contemporary Islamic schools.